Implementasi Penjatuhan Pidana Bersyarat Pada Tindak Pidana Lingkungan Hidup - Fitriani, Fitriani; Siahaan, Ade Yuliany; Hasanah, Aida Nur (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2025)
Crimes in the field of environmental protection can have vast and complex impacts/victims, as generally they not only deplete natural resources but also human capital, social capital, and even sustainable institutional capital. Criminal law plays an important role in efforts to enforce environmental law. This conditional penalty is often referred to as a probationary sentence. In the practice of criminal law in Indonesia, the imposition of conditional penalties is applied not only to human legal subjects but also to corporate legal subjects. What is questioned is the regulation of the imposition of conditional penalties and the implementation of conditional penalties for environmental crimes. This study uses a normative research method with data collection techniques, namely literature studies, with conclusions drawn using a deductive method. Conditional penalties are regulated in the Criminal Code, specifically Articles 14 (a) to 14 (f) of the Criminal Code, in the Draft Criminal Code.Conditional sentencing is aimed at specific conditions where the judge can order the defendant to provide compensation for the actions they have committed. If the compensation for the damages caused by the crime committed before the judge's decision is made, then this is a strong enough reason for the judge to impose a conditional sentence. The implementation by the judge in imposing conditional sentences on environmental offenders requires supervision by the prosecutor's office. The obstacles faced by the prosecutor's office in overseeing defendants under conditional sentences include both internal and external challenges. The Supreme Court Circular No. 7 of 1985 only contains provisions regarding the implementation of supervision and monitoring of decisions made by the judge, while the Indonesian Attorney General's Circular does not clearly state the forms of monitoring that need to be conducted by the prosecutor's office.